Evaluasi dan Rencana Pengembangan Penerapan Aplikasi Enterprise Resource Planning (ERP): Studi Kasus pada PT Astra Graphia - Wijaya, Santo Fernandi; Damayanti, Felicia Maria Cynthia (Bina Nusantara University, 2011)
A firm?s success in bussiness competition can be supported by integrated information systems. A program application based on Enterprise Resource Planning (ERP) like SAP is an integrated program that is able to provide business transaction management solutions. This study aims to on the ERP system running at PT Astra Graphia, particularly at relevant departments dealing with income derived at a period of time and costs associated with implementation and application maintenance of SAP (Systems, Applications and Products in Data Processing) program. Furthermore, this study aims to give suggestions based on information systems development evaluation results, in terms of business processes, performance, and financial. Analyses were performed using the IT Balanced Scorecard, and the development of information systems used the Accelerated SAP (ASAP) in which the results are able to provide suggestions of system development with the first phase of ASAP method namely preparation and the second phase namely blueprint.